Evidence-based practices for prevention and management of medical device alarm fatigue in anesthesia professionals - Shaoru Chen; Shaoru Chen; Shaoru Chen; Shaoru Chen; Jie Wang; Jie Wang; Jie Wang; Hui Zhi; Hui Zhi; Hui Zhi; Hui Zhi; Hongmei Zhang; et al. (Frontiers in Medicine)
ObjectiveTo assess efficacy and implement the best available evidence for managing and preventing alarm fatigue in a healthcare context.MethodsFour phases of evidence acquisition, status review, evidence application, and effect evaluation were used to apply evidence-based practice to medical care in the PACU between January and June 2024. Prior to and following the application of evidence, the occurrence of unfavorable outcomes pertaining to the management of surgical patient monitors and anesthesia alarm reports, the degree of evidence-based organizational culture, the implementation rate of review indicators, and the associated knowledge level of alarm fatigue prevention and management were all compared.ResultsFollowing the implementation of evidence-based practice, the indicators related to Anesthesiologists and nurses were reviewed, and the implementation rate was improved compared with the baseline. The frequency of negative outcomes associated with surgical patient monitoring and anesthesia alarm management was considerably decreased. Anesthesiology physicians’ and nurses’ knowledge of alarm fatigue management (t = −7.027, p < 0.001) and evidence-based practice skills (t = −52.804, p < 0.001) improved. The degree of evidence-based organizational culture was higher than baseline (t = −23.864, p < 0.001), while clinical alarm fatigue (t = 37.454, p < 0.001) and barriers to evidence-based nursing practice (t = 41.508, p < 0.001) were lower than baseline.ConclusionContinuous quality improvement is still required in subsequent clinical settings, but evidence-based practice in the Department of Anesthesiology and Perioperative Medicine can effectively standardize the alarm practice behaviors of healthcare professionals, enhance evidence-based competence, and lower the incidence of patient-related adverse events in alarm management.